2021
DOI: 10.5465/annals.2019.0057
|View full text |Cite
|
Sign up to set email alerts
|

Can High-Quality Jobs Help Workers Learn New Tricks? A Multidisciplinary Review of Work Design for Cognition

Abstract: Understanding whether and how work design affects human cognition is important because: (1) cognition is necessary for job performance, (2) digital technologies increase the need for cognition, and (3) it is vital to maintain cognitive functioning in the mature workforce. We synthesize research from work design, human factors, learning, occupational health, and lifespan perspectives. Defining cognition in terms of both knowledge and cognitive processes/fluid abilities, we show that five types of work character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 231 publications
1
26
0
2
Order By: Relevance
“…As a result, subjective feedback increases the salience of the feedback giver and may thus actually inhibit learning processes because recipients focus on receiving praise (or averting discouragement) or because they rely too strongly on guidance. Conversely, objective feedback could help recipients direct their attention toward the actual task and thereby enable learning through discovery (see also Parker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, subjective feedback increases the salience of the feedback giver and may thus actually inhibit learning processes because recipients focus on receiving praise (or averting discouragement) or because they rely too strongly on guidance. Conversely, objective feedback could help recipients direct their attention toward the actual task and thereby enable learning through discovery (see also Parker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, individuals may use subjective feedback to form impressions of the other team members, which is likely to be helpful at the beginning of virtual collaboration but which may shift the focus away from the focal task at crucial stages of task execution. Particularly when receiving output feedback, team members may thus be more likely to make judgments about the feedback giver, rather than exploring which strategies could contribute most toward improving team performance (see also Parker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We focus on perceived processing speed difficulties and organization difficulties because previous research has shown how important these components are for successful aging at work (Cheung et al, 2019;G. G. Fisher et al, 2017;Parker et al, 2021)…”
Section: A Capability Pathway Via Cognitive Constraints and Perceived...mentioning
confidence: 99%
“…, 2007). Moreover, the execution of complex tasks facilitates the application of new knowledge, skills and abilities that are important for both the generation and implementation of new ideas (Amabile, 2012; Parker et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Job design represents the content and structure of work tasks, activities, relationships and responsibilities and it's an important device for human resource management to strategically shape working practices (Parker, 2014). Job design specifically can be utilized to create a supportive and stimulating work environment that enhances IWBs (Parker et al , 2021). Numerous studies have pointed out that specific job designs can have either direct or indirect effects on individual innovation and related constructs (e.g.…”
Section: Introductionmentioning
confidence: 99%